Analisis Emoji dalam Komunikasi Non Verbal Untuk Pernyataan Perasaan Pada Komunitas Grab SGB 1B - Famelio, Apdito; Hasmawati, Fifi; Assoburu, Selvia (Indonesian Journal Publisher, 2025)
This study aims to analyze the use of emojis as a form of non-verbal communication to express feelings by members of the Grab SGB 1B community in Palembang. In the digital communication era, emojis have become an essential part of social interactions, particularly through instant messaging platforms like WhatsApp. Emojis are used to visually convey emotions and clarify the meaning of messages, thereby strengthening relationships between individuals within the community. This study used a qualitative approach with Charles Sanders Peirce's semiotic analysis method to interpret the sign meanings of emoji use by community members. Data were collected through observation and in-depth interviews with three informants. The results show that emojis are used intensively and consistently in SGB 1B community communication. Emojis are used to express moods such as humor, enthusiasm, and empathy. The use of emojis also helps avoid misunderstandings, expedites message delivery, and creates a warm and intimate communication atmosphere. Emojis have been shown to strengthen togetherness and social relationships among community members and are a crucial element in the effectiveness of digital communication.